Predictive Value of Endocan Based on TIMI Risk Score on Major Adverse Cardiovascular Events After Acute Coronary Syndrome. (November 2019) - Ziaee, Mojtaba; Mashayekhi, Sina; Ghaffari, Samad; Mahmoudi, Javad; Sarbakhsh, Parvin; Garjani, Alireza
We assessed the prognostic value of serum levels of endocan in patients with the acute coronary syndrome (ACS) through its correlation with the Thrombolysis in Myocardial Infarction (TIMI) risk score and compared the possible association with clinical outcomes. In this prospective cross-sectional study, we enrolled 320 patients with documented ST-segment elevation myocardial infarction (STEMI), non-STEMI (NSTEMI), or unstable angina (UA) who underwent diagnostic coronary angiography. Endocan was measured soon after admission in the emergency department. In-hospital death, heart failure, and recurrent infarction were considered major adverse cardiac events (MACEs). There was a significant positive correlation between endocan level and TIMI risk score and MACE. The optimal cutoff values of endocan to predict clinical end points were 3.45 ng/mL in patients with STEMI and 2.85 ng/mL in patients with UA/NSTEMI. Multivariate logistic regression analysis indicated that endocan independently correlated with MACE. Moreover, cardiac troponin I, creatine kinase-MB, and circulating endocan were found to be independently associated with MACE in patients with ACS. In conclusion, a high endocan level on hospital admission is an independent predictor of worse cardiovascular outcomes and higher TIMI risk score in patients with ACS.